ADDED VALUE OF THE COUNCIL OF EUROPE TO ADMINISTRATIVE LAW: THE DEVELOPMENT OF PAN-EUROPEAN GENERAL PRINCIPLES OF GOOD ADMINISTRATION BY THE COUNCIL OF EUROPE AND THEIR IMPACT ON THE ADMINISTRATIVE LAW OF ITS MEMBER STATES - Stelkens, Ulrich; Andrijauskaitė, Agnė (Teisė, 2017)
Although the Council of Europe has been working in the area of administrative law for decades, the body of pan-European general principles of good administration developed by this organisation remains mostly uncharted. This article attempts to help fill this academic gap by examining the scope and content of the pan-European principles of administrative law stemming from the Council of Europe, with a special emphasis on the principle of good administration. In doing so, the sources of administrative law of the Council of Europe are considered, together with the mechanisms by which they penetrate and permeate domestic legal systems. This article concludes that the work done by the Council of Europe in the administrative field has contributed to a process of harmonisation in its Member States’ domestic law, but that the exact scope thereof has yet to be uncovered and requires further research.